A conceptual model of knowledge sharing. Issue 2 (4th June 2018) - Farooq, Rayees
Abstract : Purpose: The purpose of the study is to develop a conceptual model of knowledge sharing and how knowledge sharing is linked to business performance. The study proposes basic dimensions of knowledge sharing which seem to be poorly defined in the past literature. Design/methodology/approach: The studies were explored from journals which are indexed (Scopus, Thomson Reuters and ProQuest) and specialized in knowledge sharing and business performance. Majority of the papers were available in electronic format, so that papers could be easily explored using the key terms. Various search engines were used to explore the studies such as Google scholar, Emerald insight and ProQuest. Published theses, conference proceedings, working paper series and work in progress were excluded from the search. The review process included the studies from 1987 to 2017. During the review process, papers were explored on the basis of key word search, namely, "Knowledge sharing", "Business performance" and "Industry type" to reduce interpretation bias. Findings: Knowledge sharing is the significant predictor of business performance and industry type moderates the relationship between knowledge sharing and business performance. The relationship between knowledge sharing and business performance is important in both manufacturing and service organizations. Knowledge sharing dimensions proposed are elementary in nature and require further refinement and development. Research limitations/implications: The study was approached from a theoretical perspective and the model proposed can be empirically validated by identifying statements for each dimension. Future research should explore the following: As to what extent these dimensions reflect knowledge sharing? Are dimensions chosen carefully? Or do they emerge as a result of previous studies? Practical implications: The model can be very helpful for managers and practitioners who want to study how knowledge sharing enhances business performance. Managers will be able to understand how industry-specific differences affect business performance through knowledge sharing. Originality/value: Proposed conceptual model advances the theoretical base of knowledge sharing by suggesting dimensions based on comprehensive review of the literature. The study contributes to knowledge management and business performance literature.